A multi-method investigation of the psychosocial work environment and nature of work-related stress of NHS physiotherapists and occupational therapists - Griffith-Noble, Faye (2010)
Background: The volume of empirical literature and national reports with accordance amongst findings suggests there is strong evidence for the proposition that established work-related factors for healthcare professionals may also be strong predictors of stress and associated adverse health outcomes for physiotherapists and occupational therapists employed by the NHS. The extent of published research specific to physiotherapists and occupational therapists is limited. Research targeting therapists is therefore, a prerequisite for improving knowledge and understanding the nature of therapists psychosocial work environment and work-related stress. Research objective: The objective of this research is to investigate the psychosocial work environment and nature of work-related stress of NHS physiotherapists and occupational therapists. And in doing so establish: a) how work-related stress is experienced by physiotherapy and occupational therapy employees in the NHS, and b) how we understand the determinants of stress and structural and social resources that counteract stress, and c) the implications of these for therapists' health. Research design: This programme of research is a multi-site, multi-method (quantitative and qualitative) design. It is composed of three studies each designed to make possible (in part) the overall research objective. The first study is a quantitative self-report survey of psychosocially determined work-related stress amongst NHS physiotherapists and occupational therapists. The second study is a qualitative exploration of therapists' experiences of the physical and psychosocial work environment and personal meanings prescribed to the experience of work-related stress. The third study; designed to shed light on anomalous results and findings from the first two studies, is a quantitative self-report survey of physiotherapy and occupational therapy managers' understanding and management of workplace stress. Results and findings: Study one and two suggest that the clinical psychosocial work environment of therapists is experienced as rewarding. Work-related factors, such as high work-related demands, have the potential to determine stress, but at the time of the research, were not reported to be experienced as stressful. The in-depth interviews revealed that rapid and ongoing organisational change, lack of effective top-down communication, together with issues relating to demands for heightened effectiveness were determinants of stress for NHS therapists interviewed. Results from the study one and findings from study two reveal differences in perceptions and reporting of supportive line management. Study one indicates that therapists' self-report high level of supportive line management, whilst the in-depth interviews (study two) exposed a lack of straightforward, regular, accessible instrumental and emotional line management support. Study three, found that line-managers have some or most of the knowledge required to identify, prevent and tackle stress at work. Importantly, they report an understanding of the critical role of line managers in tackling stress and appropriate line manager behaviours for minimising and managing employee stress. Conclusion: Conceptually integrated results and findings illustrate that whilst satisfied with their clinical role, therapists are experiencing work-related stress as a consequence of organisational aspects of their working environment.